OBESITY AND ITS RELATIONSHIP WITH CANCER: PART II CANCER (American International Journal of Cancer Studies, 2021)
This four-part manuscript briefly reviews the association of obesity with cancer. Part I discussed obesity while this (Part II) will discuss obesity and its impact on cancer. Part III and Part IV will review the association of obesity on fourteen common cancers.